Contours of Resistance: The Postcolonial Female Subject and the Diaspora in the Punjabi Short Story - Gill, Yubee (IAFOR journal of arts & humanities, 2021)
Diaspora literature and theory offer significant critiques of traditional ideas regarding nation-states, identities and dominant cultures. While it is true that the literature of the diaspora has been receiving increasing attention as of late, it is worth noting that works written in the diasporans’ native languages are generally not included in wider discussions about the more complex issues related to the diaspora. As an initial corrective for this deficiency, this article explores selected stories in Punjabi, paying special attention to issues relevant to the lives and experiences of women in diaspora. Diasporic conditions, as most of these stories seem to assert, can be painful for women, but even while negotiating within a diverse system of values, many of them eventually discover possibilities for independence and growth. Such personal improvements are attainable due to their newfound economic liberation, but hard-won economic independence comes with a price. The inclusivity implied by identitary hyphens (i.e. Chinese-American; Mexican-American, etc.), so celebrated in diaspora writings in English, are almost as a rule missing in the fictional accounts studied here. In these accounts, an essential feature of diasporic subjectivity is the double sense of “Otherness” strongly felt by people who, having extricated themselves from the cultural demands of their original group, are not unchallenged members of the dominant culture.